2012
DOI: 10.4161/jig.23732
|View full text |Cite
|
Sign up to set email alerts
|

The water exchange method for colonoscopy-effect of coaching

Abstract: The growing popularity of water immersion is supported by its long history as an adjunct to air insufflation; after facilitating colonoscope passage, the infused water is conveniently removed during withdrawal. Water exchange, a modification of water immersion to minimize discomfort in scheduled unsedated patients in the U.S. is new. Even though it may be superior in reducing pain and increasing adenoma detection, the paradigm shift to complete exclusion of air during insertion necessitates removal of infused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Most of the learning of WAC was based on coaching, which was an effective approach adopted by the WAC core group to expand the use of the emerging techniques. [14][15][16][17][18][19][20][21] In line with published commentaries, shorter colonoscopy time slots favored the use of WI, and longer ones increased the use of WE. 22,23 Together with data summarized in the MDCR, the current findings confirmed that the use of WAC was evolving and incorporated into research, routine practice, and teaching since the singular description of WI in 1984.…”
Section: Discussionsupporting
confidence: 55%
“…Most of the learning of WAC was based on coaching, which was an effective approach adopted by the WAC core group to expand the use of the emerging techniques. [14][15][16][17][18][19][20][21] In line with published commentaries, shorter colonoscopy time slots favored the use of WI, and longer ones increased the use of WE. 22,23 Together with data summarized in the MDCR, the current findings confirmed that the use of WAC was evolving and incorporated into research, routine practice, and teaching since the singular description of WI in 1984.…”
Section: Discussionsupporting
confidence: 55%
“…A learning curve with >90% successful cecal intubation is easily achievable after 50–100 cases [ 68 76 ]. Direct coaching by a knowledgeable trainer appears to facilitate understanding of the nuances of the WE method [ 77 ]. One approach for those who have a set number of procedures to perform on a very tight schedule is to set aside a fixed amount of time, for example, 5 min, to the per-patient allotted time to learn and practice the WE technique and then turn on the air pump when time elapses [ 69 ].…”
Section: Earning the Water Exchange Methodsmentioning
confidence: 99%
“…Compared with the water immersion method, which only infuses water without deflating the lumen,3, 4 elimination of air pockets in MWE further reduces lumen distension and loop formation. On the left side of the colon, MWE is similar to the conventional water exchange method without the need of a water pump, and faster intubation is achieved because limited air can be used from the transverse colon.…”
mentioning
confidence: 99%